Peran engagement dan religiusity terhadap job employee performance pada organisasi pemerintah - Fahmi, Moh Hisyam; Santoso, Bedjo (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
Work engagement refers to the state where employees feel a deep sense of involvement in their job, have a positive outlook towards the tasks they are assigned, and feel a strong emotional connection to the organization they are working for. In order to explore the correlation between work engagement and employee performance, a study was conducted where religiosity was taken as a moderator. The data was collected from 43 employees via questionnaires and analyzed using moderation regression. The study's findings revealed that work engagement positively impacts employee performance. However, contrary to expectations, religiosity was not a predictor or moderator of performance. More precisely, further research is necessary to investigate the relationship between religiosity and performance.